Analisa Bakteri Coliform pada Depot Air Minum Isi Ulang yang Diperjualbelikan di Jalan Benteng Hilir Tembung Medan - Silfia, Marti; Sembiring, Terang Uli. J (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Drinking water is a primary need for human life, but its quality must meet health standards to be safe for consumption. Refillable Drinking Water Depot (DAMIU) is an alternative for the community in fulfilling drinking water needs at a more affordable price. However, not all refill drinking water meets the health standards set by the Regulation of the Minister of Health of the Republic of Indonesia No. 492/MENKES/PER/IV/2010. This study aims to detect the presence of Coliform bacteria in refill drinking water sold in Jalan Benteng Hilir Tembung, Medan. The method used in this research is descriptive method with microbiological test approach using Most Probable Number (MPN). The examination was conducted at the Microbiology Laboratory of Sari Mutiara Indonesia University Medan using Lactose Broth and Brilliant Green Lactose Bile (BGLB) broth media. The samples taken were 6 samples from various refill drinking water depots in the research location. The results showed that of the 6 samples tested, 4 samples showed positive results for the presence of Coliform bacteria based on the initial test with Lactose Broth media. Furthermore, confirmation tests with BGLB media at 37°C for 1x24 hours showed MPN numbers ranging from 8.8 to 240/100 ml samples, while at 44°C for 1x24 hours, MPN numbers ranged from 10 to 27/100 ml samples. These results indicate that most of the tested refill drinking water does not meet the quality standards set by the government. The conclusion of this study is that there is Coliform bacterial contamination in some of the refill drinking water samples tested, so the water is not suitable for consumption without further treatment. Therefore, strict supervision of the quality of refill drinking water is needed as well as education to the public about the importance of consuming water that meets health standards to prevent the risk of disease due to bacterial contamination.